Writing of Hualien in Chen Li's topographical poem - Chew, Chin Chong (2013)
Poet Chen Li, who claims to be writing at the periphery of the Island of Taiwan, views the relationships between his own self and others, Hualien and Taiwan as well as Taiwan and the world from a double-peripheral perspective. This thesis adopts the theory of topographical writing to analyze Chen Li’s appreciation of the scenery and objects in Hualien as reflected in his poems. In addition, it also employs the theories of post-colonialism and post-modernism to examine Chen Li’s concern for the humanistic aspects of Hualien. Born and brought up in Hualien, Chen Li has profound emotional attachment to all things about Hualien. This thesis discusses Chen Li’s topographical construct for Hualien from two levels, i.e. the natural space and the humanistic space. Based on Chen Li’s good grasp of the topographical tempo and evidences of his endeavours to traverse to and fro across various historical trails, it can be seen that he had continually attempted to “replenish” the inherent contents of his topographical writings. Drawing from Chen Li’s works on the various aspects of the colonialists, this thesis also touches on the colonialists’ plunders of natural. resources, damages to the native people and suppression of the local mainstream. Moreover, it also discusses the mixed cultures resulting from multi-level colonial experiences. Finally, the thesis will also assess the depths and high achievements attained in Chen Li’s topographical poems about Hualien and review the “localized” and “vanguard” characteristics of his topographical poems.